The auxin transporter, OsAUX1, is involved in primary root and root hair elongation and in Cd stress responses in rice (Oryza sativa L.). (22nd July 2015) - Yu, ChenLiang; Sun, ChenDong; Shen, Chenjia; Wang, Suikang; Liu, Fang; Liu, Yan; Chen, YunLong; Li, Chuanyou; Qian, Qian; Aryal, Bibek; Geisler, Markus; Jiang, De An; et al.
Summary: Auxin and cadmium (Cd) stress play critical roles during root development. There are only a few reports on the mechanisms by which Cd stress influences auxin homeostasis and affects primary root (PR) and lateral root (LR) development, and almost nothing is known about how auxin and Cd interfere with root hair (RH) development. Here, we characterize rice osaux1 mutants that have a longer PR and shorter RHs in hydroponic culture, and that are more sensitive to Cd stress compared to wild‐type (Dongjin). OsAUX1 expression in root hair cells is different from that of its paralogous gene, AtAUX1, which is expressed in non‐hair cells. However, OsAUX1, like AtAUX1, localizes at the plasma membrane and appears to function as an auxin tranporter. Decreased auxin distribution and contents in the osaux1 mutant result in reduction of OsCyCB1;1 expression and shortened PRs, LRs and RHs under Cd stress, but may be rescued by treatment with the membrane‐permeable auxin 1‐naphthalene acetic acid. Treatment with the auxin transport inhibitors 1‐naphthoxyacetic acid and N ‐1‐naphthylphthalamic acid increased the Cd sensitivity of WT rice. Cd contents in the osaux1 mutant were not altered, but reactive oxygen species‐mediated damage was enhanced, further increasing the sensitivity of the osaux1 mutant to Cd stress. Taken together, our results indicate that OsAUX1 plays an important role in root development and in responses to Cd stress. Significance Statement: Cadmium has been shown to interfere with auxin homeostasis but the molecular mechanisms underlying responses to Cadmium stress in rice are unknown. Our analyses of mutant alleles of rice aux1, which exhibit decreased auxin levels and increased Cadmium sensitivity, highlight the importance of auxin transport during cadmium stress, and implicate a role for Reactive Oxygen Species (ROS)‐signaling.